Page 384 - diaforikos
P. 384
ΚΕΦΑΛΑΙΟ 2 - Διαφορικός Λογισμός 384
● λ=μ
● β=-4
Έτσι
lim [f(x) -(λx+β)]=0
x
νx -13x+6
2
lim [ -(μx-4)]= 0
x 3x-1
νx -13x+6-(μx-4)(3x-1)
2
lim [ ]= 0
x 3x-1 D.L.H.
(νx -13x+6-(μx-4)(3x-1))'
2
lim = 0
x (3x-1)'
2νx-13-(μx-4)'(3x-1)-(μx-4)(3x-1)'
lim = 0
x 3
2νx-13-μ(3x-1)-(μx-4)× 3
lim = 0
x 3
2νx-13-3μx+μ-3μx+12
lim = 0
x 3
2(ν-3μ)x+μ-1
lim = 0
x 3
lim[2(ν-3μ)x+(μ-1)] = 0
x
lim [2(ν-3μ)x] = 0
x
lim (μ-1) = 0
x
2(ν-3μ) = 0 (γιατι αλλιως = 0)
μ-1 = 0
ν= 3μ ν= 3
μ= 1 μ= 1
Τακης Τσακαλακος Κερκυρα 2017